Cultural Values and Job Performance of the Promotional Staff of the Department of Education, Lanao Del Sur and Marawi City, Philippines - AMPOG, ANSANO M (Jurnal Studi Pemerintahan, 2015)
The study mainly determined whether Filipino cultural values influenced the job performance of the promotional staff of the different divisions of the Department of Education in the province of Lanao Del Sur and Marawi City in the Philippines. The data gathered were analyzed using descriptive statistics, Pearson’s product-moment coefficient of correlation and t-test for correlation. Results revealed that most of the respondents were females, 31-40 years old,married, Muslims, Maranaos, permanently hired by DepEd, had master’s degrees, had been in the service for 16 years and above, and earned between P20,000.00-P24,999.00 per month, the cultural values of utang-na-loob (dept of gratitude), balikatan or bayanihan (unity or oneness), pakikitungo (smooth interpersonal relations), galang (respect), pagbabahala, pakikisama or pakikipagkapwa (concern for one another), tapang or tibay ng loob (bravery or endurance), amor propio or delicadeza (sense of propriety) and awa or malasakit (sympathy) were practiced by the respondents while their performance level was found to be very satisfactory. The test results revealed that only three socio-economic variables namely; age, sex, and length of service had significant relationship with job performance, testedat 0.05 level of significance. Moreover, seven out of the nine cultural values had significant relationships to the promotional staff’s job performance. Only amorpropio and awa or malasakit had no significant relationships to the respondents’ job performance.KEYWORDS: Cultural values, Socio – demographic profile, cultural practices, job performance, department of education